PENGARUH BUDAYA ORGANISASIONAL, LOCUS OF CONTROL TERHADAP KINERJA PEGAWAI DIMEDIASI KEPUASAN KERJA (Studi pada Dinas Pengelolaan Keuangan dan Aset Daerah Kota Semarang) - 11.42.02.0099, Adil Mumpuni Primasani (Jurnal Mahasiswa Pasca Sarjana, 2013)
In principle, performance is a result being intended by a worker on procluded criteria. In practice, however , one who implements it needs to consider some factors such as organizational culture, locus of control, and job satisfaction. The research aims to analyze direct efeects of organizatitonal culture, locus of control on employee performance. Intervening variable in this research is job satisfaction of the employee of Office for Management of Regional Finance and Assets in Semarang City. Populations of the research are derived from all employee who works at Office for Management of Regional Finance and Assets in Semarang City having been officially civil servant. There are 241 individuals who attend a purposive sampling with category are working life, grade and education is 126 of them become respondent. Models to be developed during the research are five hypothetical models, which go for validity test with component matrix, reability test with cronchbach alpha, double regresion analitical, t test and adjusted r square.The result of research indicate that variable of organizational culture, have a positive and significant influenc on job satisfaction, variable of locus of control have a positive and significant influence on job satisfaction, variable of organizational culture have not influence on employee performance, locus of control have positive and significant influence on employee performance and job satisfaction have not influence on employee performance.Implication of the policy to be proposed by manager of Management of Regional Finance and Assets in Semarang City is organizational culture, contol on lucus of control and establishment of employee job satisfaction in order to improve their performance.Â Key words : organizational culture, lcus of control, job satisfaction and employee performance